Structure and Dynamics of Elliptical Galaxies 1987
DOI: 10.1007/978-94-009-3971-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Compact Elliptical Galaxies

Abstract: In order to investigate the formation mechanisms of the rare compact elliptical galaxies (cE) we have compiled a sample of 25 cEs with good SDSS spectra, covering a range of stellar masses, sizes and environments. They have been visually classified according to the interaction with their host, representing different evolutionary stages. We have included clearly disrupted galaxies, galaxies that despite not showing signs of interaction are located close to a massive neighbour (thus are good candidates for a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 13 publications
3
45
0
Order By: Relevance
“…Thus a possible source for the star pile is obviously the CBCG itself or rather the compact dwarf cE, likely stripped by interaction with the CBCG. In fact, compact elliptical galaxies are though to form through tidal stripping (Nieto & Prugniel 1987;Bekki et al 2001).…”
Section: Star Pile and Merging Scenariomentioning
confidence: 99%
“…Thus a possible source for the star pile is obviously the CBCG itself or rather the compact dwarf cE, likely stripped by interaction with the CBCG. In fact, compact elliptical galaxies are though to form through tidal stripping (Nieto & Prugniel 1987;Bekki et al 2001).…”
Section: Star Pile and Merging Scenariomentioning
confidence: 99%
“…It is under discussion, whether environmental effects such as tidal stripping have shaped their present appearance (e.g. Faber 1973) or whether these galaxies just represent the low-luminosity end of the giant ellipticals (Nieto & Prugniel 1987). E.g., M 32 itself is a companion of the Andromeda galaxy (M 31).…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION The 32nd object in the catalog of Messier (1850) has come to be known as the archetype of high surface brightness, lowluminosity, compact elliptical galaxies (de Vaucouleurs 1961). It has been proposed that they may be the dense cores of tidally truncated, or at least modified, ordinary elliptical galaxies (King 1962;Faber 1973;Nieto & Prugniel 1987;Choi, Guhathakurta, & Johnston 2002 and references therein). It has also been suggested that M32 (NGC 221) may in fact never have been an elliptical galaxy but is instead the bulge of a (partially) stripped disk galaxy (Bekki et al 2001; see also Nieto 1990 r ral galaxy, and knowing its SMBH mass, allows one to decipher which scenario is more probable.…”
mentioning
confidence: 99%